Sarilaysay danas at dalumat ng lalaking manunulat sa Filipino - Yu, Rosario Torres 1949-; Aguirre, Alwin C.; Likhaan: U.P. Creative Writing Center (Quezon City University of the Philippines Press, 2004)
Accounts of male Filipino writers on gender politics, and arts in the Philippines.
"Sa pakikipagtulungan sa Likhaan: the UP Institute of Creative Writing"--T.p. verso.
Keywords: Tagalog literature -- Male authors -- History and criticism; Sex role -- Philippines; Art and literature -- Philippines